2019
DOI: 10.31219/osf.io/udkm2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discordance between the Sexual Experiences Surveys-Short Forms and the Revised Conflict Tactics Scales in College Men

Abstract: Objective: Sexual victimization affects at least one in five college women and up to one in six college men; however, the exact rates of sexual perpetration are difficult to ascertain because of inconsistencies in the measurement of these behaviors. The present study is the first to evaluate the extent to which three commonly used measures of sexual violence (The Sexual Experiences Survey- Short Form Victimization (SES-SFV), The Sexual Experiences Survey-Short Form Perpetration (SES-SFP) and the Revised Confli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Notably, all of these questionnaires use a tactic-first design for all or most of the items (in contrast to the SES-SFP), and many of them used a frequency scale response format that encompassed a very broad range. Anderson, Cahill, and Delahanty (2018) and Strang, Peterson, Hill, and Heiman (2013) discuss how tactic-first items, frequency scales, item order, questionnaire structure, and the assessment of consent may all be related to differences in prevalence rates obtained by measures of sexual perpetration. One of the major challenges to this literature is that different measures produce different prevalence rates, but it is unclear whether one or more of these questionnaires is the “best” or gold standard questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, all of these questionnaires use a tactic-first design for all or most of the items (in contrast to the SES-SFP), and many of them used a frequency scale response format that encompassed a very broad range. Anderson, Cahill, and Delahanty (2018) and Strang, Peterson, Hill, and Heiman (2013) discuss how tactic-first items, frequency scales, item order, questionnaire structure, and the assessment of consent may all be related to differences in prevalence rates obtained by measures of sexual perpetration. One of the major challenges to this literature is that different measures produce different prevalence rates, but it is unclear whether one or more of these questionnaires is the “best” or gold standard questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Research clearly indicates gender and sexual minorities are at much greater risk for experiencing sexual victimization (Rothman, Exner, & Baughman, 2011). Yet available measures, even those designed to be more gender-neutral (e.g., the SES-SFP), may contain unwitting heterosexist and gender bias (Anderson, Cahill, & Delahanty, 2018) that hinders further research with these populations. Finally, we came across few, if any, studies in our review that examined the sexual orientation of the target of perpetration behavior (e.g., the victim)—an area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, researchers have identified several methodological issues, such as defining the scope of sexually aggressive behavior, and wording and presenting of questions (Abbey et al, 2005; Cook et al, 2011; Koss, 1993; Krahé & Vanwesenbeeck, 2016; Krebs, 2014), which complicate the precise measurement of sexual aggression. Prevalence rates were shown to vary depending on the operational definitions of sexual aggression (see Fedina et al, 2018; Krahé et al, 2014, for reviews), and different instruments presented to the same participants yield different prevalence rates (Anderson et al, 2019a). Several analyses have shown that the use of behaviorally specific, multi-item measures is superior to broad screening questions and single-item measures (Cook et al, 2011; Krahé & Vanwesenbeeck, 2016; Krebs et al, 2017).…”
mentioning
confidence: 99%
“…For example, although the original Sexual Experiences Survey (SES) was revised to reduce gender bias (producing the Sexual Experiences Survey–Short Form Victimization [SES-SFV]), the SES-SFV does not assess forced penetration of a vagina by a penis. Furthermore, research suggests that the emphasis on sexual behaviors and descriptions of genitalia in the SES-SFV inherently genders the questionnaire which may introduce bias that decreases men’s reporting (Anderson, Cahill, & Delahanty, 2019; Anderson & Delahanty, 2019). Multiple studies have demonstrated that questionnaires which are less specific about sex and genitalia identify more cases of male sexual victimization (Anderson, Cahill, & Delahanty, 2018; Anderson & Delahanty, 2019; Struckman-Johnson et al, 2003).…”
Section: Forced Penetration and Measurement Issuesmentioning
confidence: 99%